SOCIAL ENGINEERING IN THE PROGRAM OF MATURATION OF AGE MARRIAGE - Syafei, Ermi Suhasti; Ihab Habudin (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2019)
The tradition of early marriage is a classic social problem faced by several regions. In the past four years this tradition has declined significantly, especially in Gunung Kidul, Yogyakarta. This achievement was influenced by the existence of a creative program in the form of a program of maturation of age marriage. This article explains the process of procuring a program of maturation of age marriage in Gedangsari Subdistrict, Gunungkidul Regency. The results of the study indicate the provision of a program of maturation of age marriage to prevent the occurrence of child marriage involving various related organizations and institutions. This program is very effective in reducing the rate of child marriage in Gedangsari. This program can be interpreted as social engineering so that social changes occur in the community through the process of adaptation, efforts to achieve goals, integration and latency of systems and social structures. Social engineering through law enforcement is built on rational and legal (rational-legal) arguments.